Endothelial cell culture in microfluidic devices for investigating microvascular processes - Mannino, Robert G. (Biomicrofluidics, 2018)
Numerous conditions and disease states such as sickle cell disease, malaria, thrombotic microangiopathy, and stroke significantly impact the microvasculature function and its role in disease progression. Understanding the role of cellular interactions and microvascular hemodynamic forces in the context of disease is crucial to understanding disease pathophysiology. In vivo models of microvascular disease using animal models often coupled with intravital microscopy have long been utilized to investigate microvascular phenomena. However, these methods suffer from some major drawbacks, including the inability to tightly and quantitatively control experimental conditions, the difficulty of imaging multiple microvascular beds within a living organism, and the inability to isolate specific microvascular geometries such as bifurcations. Thus, there exists a need for in vitro microvascular models that can mitigate the drawbacks associated with in vivo systems. To that end, microfluidics has been widely used to develop such models, as it allows for tight control of system inputs, facile imaging, and the ability to develop robust and repeatable systems with well-defined geometries. Incorporating endothelial cells to branching microfluidic models allows for the development of “endothelialized” systems that accurately recapitulate physiological microvessels. In this review, we summarize the field of endothelialized microfluidics, specifically focusing on fabrication methods, limitations, and applications of these systems. We then speculate on future directions and applications of these cutting edge technologies. We believe that this review of the field is of importance to vascular biologists and bioengineers who aim to utilize microfluidic technologies to solve vascular problems.